Religion in Livy - Levene, D. S. (Mnemosyne, Supplements, 1993)
This book examines the use that Livy made of religious topics, and shows how this fits in with other aspects of his narrative. The author shows how 'Livy's views of religion' depend less on personal belief than on the refinement of his narrative technique. He looks at the history decade by decade, and demonstrates that there are radical differences between different sections: in some Livy uses large-scale religious themes, but in others he deliberately avoids them. By a systematic analysis of Livy's narrative patterns and comparison with other ancient versions, it is proved that this is not simply due to subject-matter, but reflects a development in Livy's handling of his material. This profound difference between decades throws doubt on much of the standard picture of Livy: it also points to a need to revise notions of 'Augustan religious ideology'.